Social media or social menace the damage that social media may cause in language learning / Afni Anida Adnan - Adnan, Afni Anida (Universiti Teknologi MARA, Negeri Sembilan, 2024)
A quick search on the internet (Wikipedia, to be exact) lists social media as “interactive technologies that facilitate the creation, sharing and aggregation of content, ideas, cinterests, and other forms of expression through virtual communities and networks”. It goes on to add that “social media refers to new forms of media that involve interactive participation”. However, to most of us, applications or websites that may or may not encourage participation qualifies as social media. Many of us view Facebook, X (formerly known as Twitter) and TikTok as social media. These applications and sites, which mostly started as social platforms to socialize, have morphed into economic tools, with many people using them as business platforms, sometimes earning them millions of dollars (or ringgits) in mere minutes (think Khairulaming.com). Besides commercial value, these social media are also fast becoming teaching and learning tools, with many ‘teachers’, some qualified and some not, taking on the teaching scene using these platforms. While many will be quick to claim that these applications are heaven-sent to the younger generation, as they are often helmed by very attractive teachers with excellent graphic and multimedia skills to churn out equally attractive content, one must also wonder about the quality of the content that is made available.